Measurement of cerebral biomarkers proving traumatic brain injuries in post-mortem body fluids - Ondruschka, Benjamin; Sieber, Monique; Kirsten, Holger; Franke, Heike; Dressler, Jan (Journal of neurotrauma, 2018)
Until now, it is impossible to identify a fatal traumatic brain injury (TBI) before post-mortem radiological investigations or an autopsy take place. It would be preferable to have an additional diagnostic tool like post-mortem biochemistry to get greater insight into the pathological pathways and survival times after sustaining TBI. Cerebrospinal fluid (CSF) and serum samples of 84 autopsy cases were collected from forensic autopsies with post-mortem intervals (PMI) of up to 148 h. The cases were categorized into a fatal TBI case group (n=42) and non-TBI controls (n=42). The values of glial fibrillary acidic protein (GFAP), brain-derived neurotrophic factor (BDNF) and neutrophil gelatinase-associated lipocalin (NGAL) were analyzed by means of quantitative chemiluminescent multiplex immunoassays. The main results indicate that the usage of liquid samples with good macroscopic quality is more relevant for meaningful biomarker analyses than the length of the PMI. All three proteins were shown to differentiate TBI fatalities from the controls in CSF. In serum, only GFAP could be shown to be able to identify TBI cases. This study is the first approach to measure the three proteins together in CSF and serum in autopsy cases. Determined threshold values may differentiate between fatal TBI and control cases. The presented results emphasize the possible use of post-mortem biochemistry as a supplemental tool in everyday forensic routine.